Mitigation of Voltage Fluctuations using fuzzy-based D-STATCOM in High Level Penetration of DG Systems - M.Padma Lalitha; R.Madhan Mohan; B.Murali Mohan Babu (Institute of Advanced Engineering and Science, 2015)
Voltage fluctuations mainly resulting from variable output power of renewable energy sources; these are strictly challenging power quality in distribution-generation systems. The paper presents a control method for fuzzy based D-STATCOM to relieve variation of positive-sequence and negative-sequence voltages. D-STATCOM continuously operates as fundamental positive–sequence admittance and negative-sequence conductance to restore the positive-sequence voltage to the nominal value and negative-sequence voltage to the allowable level. At transient period both admittance and conductance are dynamically tuned to improve the voltage regulation performance. The ability of fuzzy logic to handle rough and unpredictable real world data made it suitable for a wide variety of applications, especially, when the models are too complex to be analyzed by classical methods. This paper presents the computer simulation of fuzzy based D-STATCOM under steady and transient state condition. The reduction of total harmonic distortions (THD) and voltage imbalance factor %VUF is discussed at all buses and maintained in acceptable level.